Development of bipolar-charged electret rotatory power generator and application in self-powered intelligent thrust bearing. (December 2021) - Tao, Kai; Zhao, Zhe; Yang, Yang; Wu, Jin; Li, Yunjia; Fan, Kangqi; Fu, Yongqing; Chang, Honglong; Yuan, Weizheng
Abstract: Inspired by an electromagnetic hydropower station that contains a reverse polarized magnet, we proposed a new design methodology of electret rotatory energy harvester (e-REH) with bipolar-charged electrets for boosting its output performance. A selectively localized corona discharging method is invented to have both positive and negative ultra-high-resolution charges implanted into a single electret thin film. A generalized theoretical model of bipolar-charged e-REHs with free-standing (Fe-REH) and sliding (Se-REH) operation modes is derived to evaluate their performance. The key features affecting their performance are the initial and parasitic capacitances with different connection schemes. Experimental results show that: the output power of the bipolar-charged e-REH is increased to 392.2% compared to those of the positive alone and negative alone configurations, which fully agree with those obtained from the theoretical model. For the first time, an intelligent thrust ball bearing is designed and fabricated with its self-powered and self-sensing capabilities based on the bipolar-charged e-REH. The rotation speed of the bearing is characterized by the response frequencies of the output voltage by Fast Fourier Transform instead of the output voltage amplitudes, exhibiting an ultra-high frequency sensitivity of 15.0 rpm/Hz and a good linearity R 2 (coefficient of determination) of 99.9%. The developed e-REH has potential applications for high-precision and self-powered intelligent rotation-speed sensing Graphical Abstract: ga1 Highlights: Achieve high-resolution bipolar-charged electrets through a selectively localized corona discharging method. Derive a generalized model to evaluate e-REH's performance with different operation modes and connection schemes. Demonstrate an intelligent thrust ball bearing with self-powered and self-sensing capabilities for the first time. Develop a frequency-related speed measurement with ultra-high sensitivity of 15.0 rpm/Hz and linearity of R 2 = 99.9%.